Implementation of The Merdeka Belajar-Kampus Merdeka Policy at The Faculty Of Islamic Religion: A Multisite Study of UMSU and UISU - Lubis, Rahmat Rifai; Wijaya, Candra; Halimah, Siti (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
This study aims to analyze the implementation of the Merdeka Belajar-Kampus Merdeka policy at the Islamic faculty of Muhammadiyah University of North Sumatra and Islamic University of North Sumatra, focusing on four things, namely implementers, targets, and management. Multicity-based qualitative research method. Data collection through observation interviews and documentation studies. The results of this study found that the implementer of MBKM in the faculty of Islam UMSU by a special MBKM unit consisting of the chairman, secretary, and members, while in the faculty of Islam UISU the implementer is the faculty and study program respectively. The targets of MBKM policy implementation in the faculties of Islam UMSU and UISU are undergraduate students in the form of the right to study three semesters outside the study program to improve hard skills and soft skills for entering the world of work. MBKM implementation management on both sites includes planning, organizing, implementing, and controlling.Â  The focus of planning on both sites becomes two namely tools and strategies. The organization of MBKM in the faculty of Islamic religion UMSU is under the coordinator of the vice chancellor III, while in the faculty of Islamic religion UISU is under the coordinator of the Chancellor. The implementation of MBKM on both sites is directed by the leadership through coaching, motivation, supervision, and evaluation. The form of policy control on both sites is the same, namely monitoring and evaluation and internal quality audits. The achievement of success in both sites has been achieved even though it is still an additional performance indicator.